Current state and prospects of land circulation in Ukraine - Marynovych, M. (Land Management, Cadastre and Land Monitoring, 2023)
The current state of agricultural land is considered destination in Ukraine after the official opening of land circulation and formed promising directions of its effective development. Generalization of factors influencing and developing land relations. The data of the State Service of Ukraine on geodesy, cartography and cadastre regarding the number of concluded deeds, as well as the area of land for which agreements were concluded by region were analyzed. The dynamics of changes in the average value of 1 ha of alienated land plots in the regions of Ukraine were monitored. The leading regions in terms of the number of alienated territories and the average cost of 1 hectare of land for commercial agricultural production were determined, and the main reasons for such variations were also clarified. Prospective ways have been formed improvement and development of market circulation of agricultural lands purposes that include: improving the integrity, accessibility and interoperability of data; optimization and improvement of assessment methods land as one of the most important steps of the State Property Fund of Ukraine; ensuring monitoring of the circulation of land plots and rights to them; magnification legal literacy and provision of legal support for citizens; adaptation and improvement of land legislation for the future functioning and development of land circulation during the period of martial law. After all, growth will depend on the efficiency of market circulation of land capacity of the population and territorial communities, as well as creation favorable conditions for the development of agrarian business in the countryside. Key words: land circulation, land reform, agricultural land, land lease, land market.